Kritik Sosial Dalam Lagu Berjudul “Revolusi” Karya Band Defamation (Analisis Wacana Kritis) - Randi Gunawan; Aka Kurnia (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This research analyzes social criticism in the lyrics of the song "Revolusi" by Dery Firmansyah (Defamation). The lyrics of this song serve as a medium for the creator to express their critical message towards the government. The research adopts a qualitative method and applies the Van Dijk Model as a framework for critical discourse analysis, particularly in understanding the structure and production processes of the text. Through discourse analysis, the study examines the elements of criticism related to the lyrics that function as a medium for criticizing the government. The main theme of the lyrics is to critique the prevailing issues at that time. The findings of the research indicate that lyrics can be used as a medium for social criticism, as evidenced by the macro structure, superstructure, micro structure, social cognition, and social context identified through text analysis.